SOLVING QUADRATIC EQUATIONS BY QUADRATIC FORMULA WORKSHEET

Solve each of the following quadratic equations using the quadratic formula.

Question 1 :

x2 – 5x – 24 = 0

Question 2 :

x2 – 7x + 12 = 0

Question 3 :

x2 – 2x - 5 = 0

Question 4 :

15x2 – 11x + 2 = 0

Question 5 :

x + ¹⁄ₓ = 2½

Question 6 :

(x + 3)2 - 81 = 0

Question 7 :

Question 8 :

 a(x2 + 1) = x(a2 + 1)

Question 9 :

3a2x2 - abx - 2b2 = 0

Question 10 :

36x2 – 12ax + (a2 - b2) = 0

tutoring.png

Answers

1. Answer :

x2 – 5x – 24 = 0

Comparing the given equation with ax2 + bx + c = 0, we get

a = 1, b = -5, c = -24

Quadratic Formula :

Substitute a = 1, b = -5 and c = -24.

x = 8  or  -3

2. Answer :

x2 – 7x + 12 = 0

From the given quadratic equation,

a = 1, b = -7, c = 12

Substitute the above values into the quadratic formula.

x = 4  or  3

3. Answer :

x2 – 2x - 5 = 0

From the given quadratic equation,

a = 1, b = -2, c = -5

Substitute the above values into the quadratic formula.

4. Answer :

15x2 – 11x + 2 = 0

From the given quadratic equation,

a = 15, b = -11, c = 2

Substitute the above values into the quadratic formula.

5. Answer :

x + ¹⁄ₓ = 2½

x + ¹⁄ₓ⁵⁄₂

Multiply both sides by 2x.

2x[x + ¹⁄ₓ] = 2x[⁵⁄₂]

2x2 + 2x(¹⁄ₓ) = 5x

2x2 + 2 = 5x

2x2 - 5x + 2 = 0

From the given quadratic equation,

a = 2, b = -5, c = 2

Substitute the above values into the quadratic formula.

6. Answer :

(x + 3)2 - 81 = 0

(x + 3)(x + 3) - 81 = 0

x2 + 3x + 3x + 9 - 81 = 0

x2 + 6x - 72 = 0

From the given quadratic equation,

a = 1, b = 6, c = -72

Substitute the above values into the quadratic formula.

x = 6  or  -12

7. Answer :

4x2 - 9x - 43 = 0

From the given quadratic equation,

a = 4, b = -9, c = -43

Substitute the above values into the quadratic formula.

8. Answer :

 a(x2 + 1) = x(a2 + 1)

 ax2 + a = xa2 + x

 ax2 + a - xa2 - x = 0

 ax2 - xa2 - x + a = 0

 ax2 - (a2 + 1)x + a = 0

From the given quadratic equation,

a = a, b = -(a2 + 1), c = a

Substitute the above values into the quadratic formula.

9. Answer :

3a2x2 - abx - 2b2 = 0

From the given quadratic equation,

a = 3a2, b = -ab, c = -2b2

Substitute the above values into the quadratic formula.

10. Answer :

36x2 – 12ax + (a2 - b2) = 0

From the given quadratic equation,

a = 36, b = -12a, c = a2 - b2

Substitute the above values into the quadratic formula.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Order of Operations Worksheet

    Jul 24, 24 03:02 AM

    orderofoperations1.png
    Order of Operations Worksheet

    Read More

  2. Order of Operations

    Jul 24, 24 03:01 AM

    order-of-operations.png
    Order of Operations - Concept - Solved Examples

    Read More

  3. PEMDAS Rule Worksheet

    Jul 24, 24 02:50 AM

    pemdas-rule-worksheet
    PEMDAS Rule Worksheet

    Read More